2018
DOI: 10.22449/1573-160x-2018-4-295-304
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Tsunami in the Black Sea Caused by the Earthquake on September 12, 1927

Abstract: Within the framework of the nonlinear model of long waves, the numerical simulation of the tsunami evolution in the Black Sea caused by the Yalta earthquake of September 12, 1927 is performed. Two problems on propagation of tsunami waves from the elliptical source are solved: for the whole Black Sea water area and for the local part of the Crimea Southern coast. The calculations for the first numerical experiment are carried out on a 30-second bathymetric grid of the Black Sea. The sea level oscillations for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Comparing the work [13] that was carried out earlier for hypothetical sources of earthquakes localized before entering the Kerch Strait, and the present work, considering seismic sources located in the south-west of the Crimean Peninsula, it was shown that in earthquakes with the same magnitudes wave heights in the strait, in particular in the Crimean Bridge area, have significantly different values. Thus, for example, the maximum wave height at the eastern pillars of the Crimean Bridge, according to [13], was 1.5 m, and, according to the computations presented in this work, the tsunami wave height from the source located in the south-west of the Crimean Peninsula, at the eastern pillars of the bridge is 0.5 m. However, in the event of a catastrophic earthquake with a magnitude of M = 8 and with a seismic source located in the zone of active faults of the Crimean Peninsula Earth's crust, in the Kerch Strait, the possible maximum wave height in the region of the western pillars of the bridge is about 0.5 m, in the region of eastern pillars up to 1.9 m. Numerical modeling of the historical earthquake of September 12, 1927 off the coast of Crimea was also carried out in [8,9,11]. Computations in these works were carried out for similar forms of the earthquake source with a magnitude of M = 7.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing the work [13] that was carried out earlier for hypothetical sources of earthquakes localized before entering the Kerch Strait, and the present work, considering seismic sources located in the south-west of the Crimean Peninsula, it was shown that in earthquakes with the same magnitudes wave heights in the strait, in particular in the Crimean Bridge area, have significantly different values. Thus, for example, the maximum wave height at the eastern pillars of the Crimean Bridge, according to [13], was 1.5 m, and, according to the computations presented in this work, the tsunami wave height from the source located in the south-west of the Crimean Peninsula, at the eastern pillars of the bridge is 0.5 m. However, in the event of a catastrophic earthquake with a magnitude of M = 8 and with a seismic source located in the zone of active faults of the Crimean Peninsula Earth's crust, in the Kerch Strait, the possible maximum wave height in the region of the western pillars of the bridge is about 0.5 m, in the region of eastern pillars up to 1.9 m. Numerical modeling of the historical earthquake of September 12, 1927 off the coast of Crimea was also carried out in [8,9,11]. Computations in these works were carried out for similar forms of the earthquake source with a magnitude of M = 7.…”
Section: Discussionmentioning
confidence: 99%
“…Computations in these works were carried out for similar forms of the earthquake source with a magnitude of M = 7. Since the Crimean Peninsula coast and the northeastern part of the Black Sea were considered in detail in [8,11], the purpose of the present research was to estimate wave characteristics in Kerch Strait water area. Here, the virtual tide gauges were put, for comparison, in [8] and [11] only a few points on the Crimean coast and only one point at the Kerch Strait (Kerch) entrance could be found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations